(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
The concepts of theoretical mechanics have been sufficiently well studied, they are used both for educational purposes and practical application. Nowadays, the use of ontologies is developing rapidly, thus allowing acquiring knowledge about the specific field of application. The author of this research analyses appropriateness of ontologies for the needs of theoretical mechanics. The study shows the use of graphs in the work with taxonomy concepts and describes the key notions of the ontologies. The author has tried to develop the concept of domain ontology for better understanding of the key notions of theoretical mechanics with a help of Protégé, which would be useful for students in the process of studying theoretical mechanics.